S-SDS : A Framework for Security Deployment as Service in Software Defined Networks, Research Gate, pp. 1-13. - Coly, Adama; Mbaye, Maissa (Research Gate, 2019)
Software Defined Networking (SDN) is an emerging networking paradigm that addresses current network design limitations. It promotes centralized control of the network by clearly separating Control Plane and Data Plane. In one hand, Security in SDN is one of the most challenging research topics. In the other hand, deployment of security as service is one of the most cutting-edge topic. In this paper, we propose a general framework for security deployment as a service in SDN networks. As a case study we proposed extension of OpenFlow protocol for IPsec VPN set. We have evaluated this proposal using a real world testbed based on Mininet and Floodlight. Preliminary results show that our proposal can enable security service without drastically degrading performance in comparison to deploy security on endpoints of communications.oftware Defined Networking (SDN) is an emerging networking paradigm that addresses current network design limitations. It promotes centralized control of the network by clearly separating Control Plane and Data Plane. In one hand, Security in SDN is one of the most challenging research topics. In the other hand, deployment of security as service is one of the most cutting-edge topic. In this paper, we propose a general framework for security deployment as a service in SDN networks. As a case study we proposed extension of OpenFlow protocol for IPsec VPN set. We have evaluated this proposal using a real world testbed based on Mininet and Floodlight. Preliminary results show that our proposal can enable security service without drastically degrading performance in comparison to deploy security on endpoints of communications.
Traditional networking appears to be reaching its limits during the late of 2010’s decade. Firstly, classical network design views networks as composed of specialized devices (router, switch, firewall, etc.) which have proprietary firmwares that include hard coded functions and forwarding logic.
Keywords: SDS; SDN; Control Plane; Data Plane; IPsec; Open Flow; Security Service Deployment; Network Security; Floodlight; Mininet